AN ANALYSIS OF STUDENTS DIFFICULTIES IN SPEAKING ENGLISH AT SMP MUHAMMADIYAH 49 MEDAN - Ade Syahputri Ritonga; Masitowarni Siregar (Universitas Negeri Medan, 2020)
Speaking seems to be the most important skills of all the four skills (listening, speaking, reading and writing), because people who know a language are usually referred to as speakers of that language. It is the means through which learners can communicative with others to achieve certain goals or to express their opinions, intentions, hopes, and viewpoints. Speaking is one of the most important skills to be developed and enhanced as means of effective communication. One of language skills that should be mastered by students is speaking. Speaking skill is regarded one of the most difficult aspects of language learning. Therefore, to overcome this problem, the researcher agreed to conduct a study entitled “An Analysis of Students Difficulties in Speaking English at Smp Muhammadiyah 49 Medan”.